PERSPEKTIF SENI DALAM ISLAM : PELATIHAN HADRAH PADA ANAK – ANAK DI DUSUN KALITELON RT 03 RW 04 KALIGENTONG, GLADAKSARI , BOYOLALI - AGUS SETYO WARDOYO; ADHIPUTRO PANGARSO WICAKSONO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Islamic culture is a culture that emerges, emanates from Islam, or all cultures (human works) that are influenced by the existence of Islam. Human work in Islamic culture is a dynamic method of implementation, while the principles come from God and are permanent. A person in his life must have guidelines and visions to establish himself from the pace of progress in modern times, students are educated and taught the values ​​of Islamic culture so that they can have broad insight and can reflect Islamic values ​​in their daily life. In improving this, a person should be able to be more critical and also careful on several new things as well as find ways to filter things that have positive and negative impacts and religion to become the main foundation for oneself in order to control oneself. The hadith about the virtue of reading the Prophet's prayers has penetrated the souls of the people of Kalitelon Rt.03 Rw.04 Kaligentong Village. The community has increasingly enjoyed hadroh and shalawatan training which are held every week. This social phenomenon implies that religion is an important indicator. Especially the traditions relating to commands and fadhilah (virtue) to pray to the prophet. This forms the mindset and religious spirit of the people of Kalitelon Rt.03 Rw.04 Kaligentong Village, Gladaksari District, Boyolali Regency. This phenomenon is also known as the living hadith phenomenon. The phenomenological approach with functional theory is the focus of this research. It can be concluded that this phenomenon is a tradition that develops in society. This study is considered to be a contemporary hadith study that can shift the existence of previous hadith studies.